The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s1415-47572010005000063
|View full text |Cite
|
Sign up to set email alerts
|

Co-localization of GSTP1 and JNK in transitional cell carcinoma of urinary bladder

Abstract: Transitional cell carcinoma (TCC) of urinary bladder belongs to glutathione S-transferase P1 (GSTP1) overexpressing tumors. Upregulated GSTP1 in TCC is related to apoptosis inhibition. This antiapoptotic effects of GSTP1 might be mediated through protein:protein interaction with c-Jun NH2 -terminal kinase (JNK). Herein, we analyzed whether a direct link between GSTP1 and JNK exists in TCC. The presence of GSTP1/JNK complexes was analyzed by immunoprecipitation and Western blotting in 20 TCC specimens, obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…In TCC, it can be speculated that increased GSTO1 expression through its deglutathionylase activity keeps the GSTP1 in complex with JNK, contributing to the apoptosis resistance. Indeed, the existence of GSTP1: JNK interaction in both TCC 5637 cell line and TCC tumor tissue was confirmed in our earlier investigation [19], while in the current study, we have shown, for the first time, the association between GSTO1 and GSTP1 by immunoprecipitation. Additionally, we have looked for the possible association of GSTO1-1 with some of the signaling molecules of PI3K and MAPK pathways known to be regulated by S-glutathionylation.…”
Section: Discussionsupporting
confidence: 90%
“…In TCC, it can be speculated that increased GSTO1 expression through its deglutathionylase activity keeps the GSTP1 in complex with JNK, contributing to the apoptosis resistance. Indeed, the existence of GSTP1: JNK interaction in both TCC 5637 cell line and TCC tumor tissue was confirmed in our earlier investigation [19], while in the current study, we have shown, for the first time, the association between GSTO1 and GSTP1 by immunoprecipitation. Additionally, we have looked for the possible association of GSTO1-1 with some of the signaling molecules of PI3K and MAPK pathways known to be regulated by S-glutathionylation.…”
Section: Discussionsupporting
confidence: 90%
“…Since UC is often associated with exposure to carcinogens, researchers have evaluated the use of the GST genotype for stratifying UC risk (Kempkes et al, 1996). Other studies have investigated either GST genetic polymorphisms or tissue-specific GST expression in bladder cancer (Giralt et al, 1993;Pljesa-Ercegovac et al, 2010;PljesaErcegovac et al, 2011). Although the GST isoenzyme pattern in UC resembles that of the corresponding normal uroepithelium, the increased expressions of all GST subtypes reportedly correspond with progression of the cancer (Simic et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The research interest in GSTP1 covers last 22 years with a peak in 2012. GSTP1 widely represented in oncology connecting oxidative stress, apoptosis and carcinogenesis [ 147 , 148 , 149 ], but also plays a role in asthma [ 150 ], Parkinson’s disease [ 151 ]. Kidney damage was also reported in conjunction, however much less supported [ 151 ].…”
Section: Regulatory Pathways and Antioxidative Therapiesmentioning
confidence: 99%